Crosstalk Between ROS and Autophagy in Tumorigenesis: Understanding the Multifaceted Paradox - Hasan, Adria; Rizvi, Suroor Fatima; Parveen, Sana; Pathak, Neelam; Nazir, Aamir; Mir, Snober S. (Frontiers in Oncology, 2022)
Cancer formation is a highly regulated and complex process, largely dependent on its microenvironment. This complexity highlights the need for developing novel target-based therapies depending on cancer phenotype and genotype. Autophagy, a catabolic process, removes damaged and defective cellular materials through lysosomes. It is activated in response to stress conditions such as nutrient deprivation, hypoxia, and oxidative stress. Oxidative stress is induced by excess reactive oxygen species (ROS) which are multifaceted molecules that drive several pathophysiological conditions, including cancer. Moreover, autophagy also plays a dual role, initially inhibiting tumor formation but promoting tumor progression during advanced stages. Mounting evidence has suggested intricate crosstalk between autophagy and ROS where they can either suppress cancer formation or promote disease etiology. This review highlights the regulatory roles of autophagy and ROS from tumor induction to metastasis. We also discuss the therapeutic strategies that have been devised so far to combat cancer. Based on the review, we finally present some gap areas that could be targeted and may provide a basis for cancer suppression.